2019
DOI: 10.1016/j.sjbs.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the response of soil and vegetable crops to poultry and cow manure using ground and satellite data

Abstract: Based on the massive production of cow and poultry manures, farmers in Saudi Arabia are moving towards the application of organic fertilizers in their farms. Therefore, the present work was conducted to study the response of soil and selected vegetable crops to poultry and cow manures, using ground data and Landsat-8 and Hyperion images. The studied vegetable crops are cabbage, cauliflower, broccoli, and lettuce. A total of 100 t ha−1 organic manures were applied as a pre-planting treatment. A 12.5 ha field in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…(2017) who noted a significant improvement of yam yield due to the application of a mixture of green manure and poultry manure. Likewise, Al-Gaadi et al. (2019) in the central region of Saudi Arabia, has reported that crop yields performed better with the application of organic fertilizers such as poultry manure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…(2017) who noted a significant improvement of yam yield due to the application of a mixture of green manure and poultry manure. Likewise, Al-Gaadi et al. (2019) in the central region of Saudi Arabia, has reported that crop yields performed better with the application of organic fertilizers such as poultry manure.…”
Section: Discussionmentioning
confidence: 98%
“…Organic manures have been recommended as alternative to mineral fertilizers for improving soil productivity in agricultural systems in Africa because of their beneficial effects on soil productivity ( Harraq et al., 2021 ; Ravindran et al., 2017 ; Adekiya and Agbede, 2016 ). Their effects include improvement of soil physical and chemical properties and crops yield ( Al-Gaadi et al., 2019 ; Biratu et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings agreed with those of Agbede et al 32 , who observed significant improvement of yam yield due to the application of a mixture of green manure and poultry manure in Nigeria. Also, Al-Gaadi et al 33 in the central region of Saudi Arabia and Biratu et al 17 , reported that crop yields were better with the application of organic fertilizers such as poultry manure.…”
Section: Discussionmentioning
confidence: 99%
“…Indeks pH tanah semakin meningkat seiring dengan tingginya dosis kotoran kandang ayam dibandingkan kotoran kandang sapi. Diketahui bahwa kotoran ayam lebih banyak mengandung basa-basa kation yang mampu meningkatkan KTK dibandingkan kotoran kandang sapi (Al-Gaadi et al, 2019). Hasil uji BNT α 5 % menunjukkan indeks pH tanah tertinggi pada perlakuan P3 dan sama dengan perlakuan P2 dan P1, namun berbeda dengan P0 (Gambar3).…”
Section: Ph Tanah Yang Diberi Perlakuanunclassified